2004
DOI: 10.1128/jb.186.1.192-199.2004
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Catabolic Protein Expression during Anaerobic Growth of Escherichia coli K-12

Abstract: During aerobic growth of Escherichia coli, expression of catabolic enzymes and envelope and periplasmic proteins is regulated by pH. Additional modes of pH regulation were revealed under anaerobiosis. E. coli K-12 strain W3110 was cultured anaerobically in broth medium buffered at pH 5.5 or 8.5 for protein identification on proteomic two-dimensional gels. A total of 32 proteins from anaerobic cultures show pH-dependent expression, and only four of these proteins (DsbA, TnaA, GatY, and HdeA) showed pH regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
74
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 61 publications
10
74
1
1
Order By: Relevance
“…In addition, an integrated analysis of metabolites and transcripts revealed that metabolic pathways that have been assumed to regulate cytosolic pH of the plant (biochemical pH stat [Sakano, 1998] and g-aminobutyric acid [GABA] shunt [Bouche and Fromm, 2004] pathways) were also down-regulated in the mutant. Interestingly, both ion homeostasis and pH-regulating metabolism are critical for low pH resistance in other organisms, such as Escherichia coli (Yohannes et al, 2004) and fish (Hirata et al, 2003) and possibly in higher plants (Yan et al, 1992). These results indicated that STOP1 regulates multiple tolerant mechanisms to major stress factors of acid soil and that some of the H 1 -resistant systems down-regulated in the stop1 mutant are similar to those of other organisms.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In addition, an integrated analysis of metabolites and transcripts revealed that metabolic pathways that have been assumed to regulate cytosolic pH of the plant (biochemical pH stat [Sakano, 1998] and g-aminobutyric acid [GABA] shunt [Bouche and Fromm, 2004] pathways) were also down-regulated in the mutant. Interestingly, both ion homeostasis and pH-regulating metabolism are critical for low pH resistance in other organisms, such as Escherichia coli (Yohannes et al, 2004) and fish (Hirata et al, 2003) and possibly in higher plants (Yan et al, 1992). These results indicated that STOP1 regulates multiple tolerant mechanisms to major stress factors of acid soil and that some of the H 1 -resistant systems down-regulated in the stop1 mutant are similar to those of other organisms.…”
supporting
confidence: 52%
“…Interestingly, orthologs of these genes have been identified as critical for adaptation to acidic environments in other organisms (Castanie-Cornet et al, 1999). For E. coli, GAD is essential for surviving in low-pH medium (Yohannes et al, 2004). These genes, which are down-regulated in the stop1 mutant, could be involved in low-pH-tolerant mechanisms in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reactions that were significantly regulated by the control of enzyme activity, we identified reactions in which our results agreed with the previous case studies (6,(19)(20)(21)(22)(23)(24)(25) by looking for perturbations that had high significance scores. Following anaerobic perturbation, we identified significant reactions that are related to the central metabolism.…”
Section: Resultssupporting
confidence: 82%
“…This might be due to the test bacterium was a clinical isolate and preferred the conditions close to that of the human intestine (neutral pH). In E. coli, it has been found that alkalinity could induce the expression of tnaA gene leading to high tryptophanase activity and active indole production [13,28,29]. In this study, we found that at pH 7, all clinical isolates of V. cholerae and environmental isolates produced similar amounts of indole, although indole production in one environmental isolate was significantly different ( Table 1).…”
Section: Resultsmentioning
confidence: 48%